ANALISIS PENGGUNAAN E-COMMERCE DALAM MENINGKATKAN PENJUALAN UMKM DI ERA DIGITAL - Sariyani Sariyani; Muhammad Irwan Padli Nasution (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to analyze the use of e-commerce in increasing MSME sales in the digital era. The main focus of this research is to identify the benefits that MSMEs gain from using e-commerce as well as the challenges they face. Indonesian people are increasingly familiar with the use of the internet, so they understand internet-based trading activities. The use of e-commerce has a role in changing the paradigm of a business. Business actors must understand and be able to apply the electronic sales system or e-commerce so that they are not left behind by other business people who have used the e-commerce system. This research method uses a literature study that uses previous literature related to the research topic. The results obtained in this study are that e-commerce is a necessity for MSMEs to improve and win business competition and product sales and make a significant contribution to the growth of MSMEs in terms of increasing revenue. The benefits that can be felt by MSMEs in using e-commerce are sales growth and market growth. However, in addition to obtaining benefits, there are certainly challenges that must be faced by MSMEs, namely, low digital literacy, limited infrastructure, and intense competition.